THEORETICAL FOUNDATIONS OF THE CREDIT MECHANISM OF MEETING CONSUMER NEEDS OF THE POPULATION - Харабара, Віолетта; Грешко, Роман Ігорович (Three Seas Economic Journal, 2020)
Purpose. A significant role in ensuring the socio-economic development of the state, increasing the economic activity and purchasing power of the population is played by the credit mechanism of meeting the consumer needs of the population. However, the effects of crisis phenomena in the state economy have created high credit risks, which negatively affected the dynamics of consumer lending in Ukraine. Method. Thus, the purpose of this article is to study the financing of the real sector of the economy and increase its capital due to the effective functioning of the credit mechanism of meeting the consumer needs of the population. Research results. The theoretical approaches of scientists to the essence, elements and components of the credit mechanism of meeting the consumer needs of the population, external and internal factors influencing its efficiency, such as the ability of the borrower to return the credit, availability of credit, interest rate, as well as maturity and repayment terms are investigated in the paper. Also, the study analyzed legislative and regulatory acts on the development of credit relations and the banking system in Ukraine. The problems of organization of credit activity of banks, formation of effective credit policy, choice of effective methods, types of lending are considered. Particular attention is paid to the most common type of crediting of consumer needs with credit cards in the modern way. Value/originality. As a result, the paper proposes to consider the essence of the credit mechanism of meeting the consumer needs of the population as a set of forms and tools for influencing the system of credit relations between the subjects of lending to the consumer needs in order to provide the necessary volumes of consumer credit. In turn, as a result of using the method of comparative analysis, the list of consumer lending facilities is systematized in the work, the classification of credits for consumer needs of the population is improved, and the author’s vision of the main components of the credit mechanism of meeting the consumer needs of the population is characterized.
Keywords: credit relations; consumer needs; credit policy; banks; Ukraine